Implementing Mobile IP Scenario Using NS-2 - Jajula, Jalandher (My University, 2010)
The number of wireless networks is increasing day by day as a result of it more number of users are opting for the wireless technology. The emergence of mobile devices or mobile nodes allows the users to access the network when they are on the move. As users move frequently from one network to another network a new IP address is assigned to the mobile node every time when it visits a new network. The mobile node has no way to inform the change in its IP address to the other nodes present in the network to which it belongs so the packets sent to the mobile node previous IP address are simply lost. To deal with the change in the IP addresses of the mobile node every time it visits a new network can be handled by the Mobile IP. Mobile IP is a protocol, developed by the Mobile IP Internet Engineering Task Force (IETF) working group that allows the delivery of the packets to mobile nodes when they moves to a new network based on its old IP address. In this thesis work an attempt has been made to simulate the mobile IP scenario with the use of NS-2 network simulator.
M.E. (Software Engineering)
Keywords: MOBILE IP,HOME AGENT ,FOREIGN AGENT,NS2